NLRX1 limits inflammatory neurodegeneration in the anterior visual pathway - Alexander J. Gill; Matthew D. Smith; Danny Galleguillos; Thomas Garton; Jackson W. Mace; Sachin P. Gadani; Swati Kumar; Aayush Pokharel; Krista Solem; Saahith Potluri; Omar Hussein; Giuliana Sardi Rogines; et al. (Journal of Neuroinflammation)
Abstract Chronic innate immune activation in the central nervous system (CNS) significantly contributes to neurodegeneration in progressive multiple sclerosis (MS). Using multiple experimental autoimmune encephalomyelitis (EAE) models, we discovered that NLRX1 protects neurons in the anterior visual pathway from inflammatory neurodegeneration. We quantified retinal ganglion cell (RGC) density and optic nerve axonal degeneration, gliosis, and T-cell infiltration in Nlrx1 −/− and wild-type (WT) EAE mice and found increased RGC loss and axonal injury in Nlrx1 −/− mice compared to WT mice in both active immunization EAE and spontaneous opticospinal encephalomyelitis (OSE) models. To minimize the effects of Nlrx1 −/− on peripheral lymphocyte priming during EAE, we performed adoptive transfer experiments, in which activated myelin-specific T cells were transferred into lymphocyte-deficient Rag −/− or Nlrx1 −/− Rag −/− mice. In this model, we found more severe microgliosis and astrogliosis in the optic nerve of Nlrx1 −/− Rag −/− mice compared to Rag −/− mice, suggesting a regulatory role of NLRX1 in innate immune cells. Transcriptome analysis in primary astrocytes activated with LPS and IFNγ demonstrated that NLRX1 suppresses NF-κB activation and regulates mitochondrial oxidative phosphorylation in inflammatory reactive astrocytes. The novel pharmacologic NLRX1 activators NX-13 and LABP-66 decreased LPS-mediated gene expression of inflammatory cytokines and chemokines in mixed glial cultures. Moreover, treating EAE mice with oral LABP-66, compared to vehicle, after the onset of paralysis resulted in less anterior visual pathway neurodegeneration. These data suggest that pharmacologic NLRX1 activators have the potential to limit inflammatory neurodegeneration. This study highlights that NLRX1 could serve as a promising target for neuroprotection in progressive MS and other neurodegenerative diseases. Further studies are needed to better understand the cell-specific mechanisms underlying the neuroprotective role of NLRX1 in response to inflammation in the CNS.